Odpowiedź :
Cześć!
Obliczenia
[tex]3^2\cdot(\frac{1}{9})^7:(\frac{1}{3})^4=3^2\cdot((\frac{1}{3})^2)^7:((\frac{1}{3})^1)^4=3^2\cdot(3^{-2})^7:(3^{-1})^4=\\\\=3^2\cdot3^{-2\cdot7}:3^{-1\cdot4}=3^2\cdot3^{-14}:3^{-4}=3^{2+(-14)}:3^{-4}=\\\\=3^{2-14}:3^{-4}=3^{-12}:3^{-4}=3^{-12-(-4)}=3^{-12+4}=\boxed{3^{-8}}[/tex]
Wykorzystane wzory
[tex](a^m)^n=a^{m\cdot n}\\\\a^{-n}=(\frac{1}{a})^n\\\\a^m\cdot a^n=a^{m+n}\\\\a^m:a^n=a^{m-n}[/tex]
Odpowiedź:
[tex]3^2\cdot(\frac{1}{9})^7:(\frac{1}{3})^4=(\frac{1}{3})^{-2}\cdot((\frac{1}{3})^2)^7:(\frac{1}{3})^4=(\frac{1}{3})^{-2}\cdot(\frac{1}{3})^{14}:(\frac{1}{3})^4=(\frac{1}{3})^{-2+14-4}=\\\\=(\frac{1}{3})^8=\frac{1}{6561}[/tex]